Surgical Removal of Midurethral Sling in Women Undergoing Surgery for Presumed Mesh-Related Complications: A Systematic Review. Issue 2 (February 2022) - Doyle, Paula Jaye; Grimes, Cara L.; Balk, Ethan M.; Wieslander, Cecilia; Richardson, Monica; Mamik, Mamta M.; Sleemi, Ambereen; Alas, Alexandriah; Kudish, Bela; Walter, Andrew J.; Aschkenazi, Sarit; Mama, Saifuddin; et al.
Abstract : OBJECTIVE: To assess whether some, or all, of the mesh needs to be removed when a midurethral sling is removed for complications. DATA SOURCES: A systematic review and meta-analysis was conducted. MEDLINE, Cochrane, and ClinicalTrials.gov databases from January 1, 1996, through May 1, 2021, were searched for articles that met the eligibility criteria with total, partial, or a combination of anti-incontinence mesh removal. METHODS OF STUDY SELECTION: All study designs were included (N≥10), and a priori criteria were used for acceptance standards. Studies were extracted for demographics, operative outcomes, and adverse events. Meta-analysis was performed when possible. TABULATION, INTEGRATION, AND RESULTS: We double-screened 11, 887 abstracts; 45 eligible and unique studies were identified. Thirty-five were single-group studies that evaluated partial mesh removal, five were single-group studies that evaluated total mesh removal, and five were studies that compared partial mesh removal with total mesh removal. All of the studies were retrospective in nature; there were no randomized controlled studies. Comparative studies demonstrated that partial mesh removal had lower rates of postoperative stress urinary incontinence (SUI) than total mesh removal (odds ratio 0.46, 95% CI 0.22–0.96). Single-group studies supported lower rates of postoperative SUI with partial mesh removal compared with total mesh removal (19.2% [95% CI 13.5–25.7] vs 48.7% [95% CI 31.2–66.4]). Both methods were similar with respect to associated pain, bladder outlet obstruction, mesh erosion or exposure, and lower urinary tract symptoms. Adverse events were infrequent. CONCLUSION: Postoperative SUI may be lower with partial mesh removal compared with total mesh removal. Other outcomes were similar regardless of the amount of mesh removed. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD 42018093099. Abstract : Postoperative stress urinary incontinence may be lower with partial mesh removal compared with total mesh removal; other outcomes are similar regardless of the amount of mesh removed.